The relationship of the maternal-fetal attachment and the attitude toward exclusive breastfeeding among pregnant women in Indonesia - Wahidah Sukriani; Endang Koni Suryaningsih; Nguyen Dieu Linh (Journal of Health Technology Assessment in Midwifery, 2020)
Compare to others province in Borneo, central Borneo has fail to meet the minimum target of exclusive breastfeeding, estimated only about 20.5%. However, in Palangka Raya City, the prevalence of exclusive breastfeeding roughly only 14.99% and this number has decreased slowly year by year. Maternal Fetal Attachment (MFA) is playing an important role to the mother’s attitude to breastfeed their babies when they birth. Maternal-fetal attachment also affected to the mother’s health practice attitude toward her pregnancy. The aimed of this study is to explore the relationship between maternal-fetal attachment and their attitude toward breastfeeding exclusively. The consecutive sampling was used to recruited 97 participants in this study. Rank spearmen was calculated to determine the relationship between two variables. The result finding there is no a significant relationship between maternal-fetal attachment and their attitude to breastfeed exclusively. Limitations and recommendations have been made in this article for further study in the same area.